Viral‐associated trichodysplasia spinulosa in a paediatric cardiac transplant recipient. (20th June 2019) - Stephan, C.; Kurban, M.; Khalil, S.; Bitar, F.; El‐Rassi, I.; Assy, J.
Abstract : Click here for the corresponding questions to this CME article.